Clinical Application of Magnifying Endoscopy with Narrow-Band Imaging in the Stomach - Kenshi Yao (Korean Society of Gastrointestinal Endoscopy, 2015)
Magnifying endoscopy with narrow-band imaging (M-NBI) can visualize superficial microanatomies in the stomach. The normal morphology of the microanatomy visualized by M-NBI differs according to the part of the stomach. The gastric fundic glandular mucosa appears as a regular honeycomb-like subepithelial capillary network (SECN) pattern with a regular collecting venule pattern and regular oval crypt opening with circular marginal crypt epithelium (MCE) pattern. The gastric pyloric glandular mucosa displays a regular coil-shaped SECN pattern and regular polygonal or curved MCE pattern. For a diagnosis of early gastric cancer using M-NBI, the vessel plus surface classification system was developed. This system is clinically useful for the differential diagnosis of focal gastritis and small depressed cancer and for determining the horizontal extent of early gastric cancer for successful endoscopic resection. Advantages of M-NBI over conventional endoscopic imaging techniques with white light include accurate diagnosis and cost effectiveness. This technique is a breakthrough in the endoscopic diagnostic field.